catena-Poly[[[diaquasodium]-di-μ-aqua] 2-(2-pyridyl)quinoline-4-carboxylate] - Hao, Hu-Jun (International Union of Crystallography, 2010)
In the title compound, [Na(H(2)O)(4)](C(15)H(9)N(2)O(2)), the Na(+) ion is coordinated by six water molecules in an octahedral geometry. The NaO(6) octahedra are connected by sharing edges, forming a cationic chain along the b-axis direction. O—H⋯O and O—H⋯N hydrogen bonds link the chains and the 2-(2-pyridyl)quinoline-4-carboxylate anions into a two-dimensional network parallel to (100).